Pelatihan Dan Pendampingan Laporan Keuangan: Upaya Mendorong UMKM Naik Kelas - Kurniawati, Lestari; Mahrus, M. Luthfi; Indrawati, Iin; Nugrahanto, Fajar Yudha; Afliah, Nada Zalza (Pengmasku, 2024)
The vision of the South Tangerang City Government is to make MSMEs a prima donna not only in South Tangerang City, experiencing problems including the limitations of MSMEs in making financial reports so that an overview of the financial performance and wealth of MSMEs is not obtained. An overview of performance through financial reports is a prerequisite for applying for MSME financing. Training and assistance in the preparation of financial reports is an effort by the South Tangerang City Government and PKN STAN so that MSMEs are promoted through an understanding of the financial performance of the business being managed and the opportunity to obtain financing. Training on preparing Financial Reports is carried out in masse for all MSMEs and intensively with division into groups. Meanwhile, assistance is provided intensively and continuously for two MSMEs, Idea Mulya and Cilok Djoedes. Obstacles such as the readiness of MSMEs to prepare financial transaction data still arise during mentoring. In addition, problems related to the SIAPIK application still arise, such as difficulties in recording past transactions, determining the final consignment balance value, and recording product sales in retail. However, the training and mentoring went smoothly and provided positive benefits for MSMEs in their efforts to realize MSMEs promotion to class.